A COMPARATIVE STUDY ON CONSUMER BEHAVIOUR IN PURCHASING ESSENTIAL GOODS DURING COVID19: EVIDENCE FROM COIMBATORE DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
A consumer is the king in a free market economy. The earlier approach of ‘caveat emptor’ - Let the buyer beware, has now shifted towards ‘caveat venditor’ – Let the seller beware. Consumer purchasing behavior also known as consumer buying behavior, refers to the behavior of a person before purchasing a product or a service. It involves various activities carried out by the customers before procurement of goods.The consumer buying behavior is mainly based on two factors:• Degree of buyer involvement• Degree of differences among brandsOn the basis of these factors, the buying decision behavior can be separated into 4 categories.The year 2020 will go down in the history of retail as a year of overcoming problems and opening new possibilities. One of the benefits of an otherwise unfavorable situation is the fact that customers have begun to realize how important retail is to their daily lives. Covid-19 has changed the world of retail and the customer. Based on the comparison with the previous period, there was an increase in average spending and a decrease in the frequency of purchases. Consumer confidence has fallen; people are worried about the future. Retailers have invested billions in ant coronary measures and E-commerce is breaking records.